Cover Feature: Dimorpholinoacetylene and Its Use for the Synthesis of Tetraaminocyclobutadiene Species (Chem. Eur. J. 65/2022). Issue 65 (8th November 2022) - Körner, Lukas; Ho, Luong Phong; Puchta, Ralph; Stanger, Amnon; Tamm, Matthias
Abstract : A stable cyclobutadiene dication was isolated and structurally characterized as a bis(tribromide) salt. Unlike the folded minimum structure calculated for the parent C4 H4 2+ system, this dication exhibits a planar geometry in the solid state. However, calculations reveal a nearly isoenergetic folded isomer, and detailed studies employing advanced NICS methods show that, counterintuitively, cyclobutadiene dications are more aromatic when puckered rather than planar. For more information on this topic and related applications of diaminoacetylenes, see the Research Article by M. Tamm and co‐workers (DOI: 10.1002/chem.202202737 ).